Studies on Canning of Mackerel Fillets in Oil - SARALAYA, K V; PARASHURAM, P; RAI, B S (Fishery Technology, 1975)
Canning operations suitable for packing mackerel ( Rastrelliger kanagurta) in the form of skinless and boneless fillets in oil were studied and the process standardised. The technique of lye peeling for skin removal could be successfully applied. The storage life of the final product was tested over a period of mie year and found to be quite comparable to other similar fish products.